2021
DOI: 10.3233/jvr-211151
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the job accommodation needs of American workers with mid-career neurological disabilities: A multiple case study investigation

Abstract: METHODS: Four employed people with neurological disabilities who took part in a larger job retention project funded by the United States Department of Labor completed structured interviews to determine their needs for employment accommodations during COVID-19. A trained interviewer administered the Work Experience Survey (WES) in teleconsultation sessions with each participant to identify: (a) barriers to worksite access, (b) difficulties performing essential job functions, (c) concerns regarding continued job… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…The findings indicate that competence in individually evaluating the impact of various cognitive impairments and how these can be reduced by self-management strategies and adjustments in work is needed. This is in line with research highlighting the need of including professionals with expertise in rehabilitation to facilitate a supportive work environment [45,46].…”
Section: Discussionsupporting
confidence: 84%
“…The findings indicate that competence in individually evaluating the impact of various cognitive impairments and how these can be reduced by self-management strategies and adjustments in work is needed. This is in line with research highlighting the need of including professionals with expertise in rehabilitation to facilitate a supportive work environment [45,46].…”
Section: Discussionsupporting
confidence: 84%
“…One potential way to address the inequities in the availability of work from home options would be to implement more permanent legislation explicitly making the option a right for all workers, as a few of the studies in our review observed [28,37,47,62]. Rumrill et al suggest that permanently allowing pandemic-era remote work for all, regardless of disability status, would be one way to implement the…”
Section: Discussionmentioning
confidence: 93%
“…universal design principle in employment legislation [37]. Such legislation could potentially eliminate the need for disclosure among workers with disabilities who require remote work, thus removing one of the common barriers to receiving workplace accommodation that has been identified in previous studies and reviews [18,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We must perform excellent work that is crucial for ourselves and others. (Rumrill et al, 2021). Mastery of work and the use of tools by a worker are specific determinants of the quality of work (Krichene and Baklouti, 2021).…”
Section: Introductionmentioning
confidence: 99%